Biodegradable Scaffolds for Bone Regeneration Combined with Drug-Delivery Systems in Osteomyelitis Therapy - Rossella Dorati; Antonella DeTrizio; Tiziana Modena; Bice Conti; Francesco Benazzo; Giulia Gastaldi; Ida Genta (MDPI AG, 2017)
A great deal of research is ongoing in the area of tissue engineering (TE) for bone regeneration. A possible improvement in restoring damaged tissues involves the loading of drugs such as proteins, genes, growth factors, antibiotics, and anti-inflammatory drugs into scaffolds for tissue regeneration. This mini-review is focused on the combination of the local delivery of antibiotic agents with bone regenerative therapy for the treatment of a severe bone infection such as osteomyelitis. The review includes a brief explanation of scaffolds for bone regeneration including scaffolds characteristics and types, a focus on severe bone infections (especially osteomyelitis and its treatment), and a literature review of local antibiotic delivery by the combination of scaffolds and drug-delivery systems. Some examples related to published studies on gentamicin sulfate-loaded drug-delivery systems combined with scaffolds are discussed, and future perspectives are highlighted.